Ewolucja greckich środków społecznego przekazu, z uwzględnieniem komunikatu reklamowego - Grochowski, Robert (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
In terms of the means of social communication, Greece is a unique country. Its media system has been significantly influenced by the culture and history of political and social relations. Radio and press emerged at a time of warfare and the struggle for independence, whereas television began and developed in the period of political conflict in the 20th century, which is still evident in Greek public television. Regulations concerning the media are not fully observed there. This also refers to the advertising messages broadcast mainly by private television channels. The EU legislation Greece adopted is not fully obeyed by the media, or the advertising industry either. The paper outlines the history and importance of the Greek mass media, the advertising policy of some television stations and also refers to large format advertising. It should be pointed out that the facts and conclusions presented by the author with reference to advertising messages and television come from the research he conducted in Greece from 2008 through 2010.